Wayang Wong Lakon Lumbung Tugu Mas dalam Ritus Suran Desa Tutup Ngisor, Magelang - Dwi Wahyudiarta (Greget, 2009)
The story of Lumbung Tugu Mas in the Javanese stage show (wayang wong) in the Suran ceremony in Tutup Ngisor village, Magelang, is believed to have the power to expel evil spirits, and has an important meaning for the community, giving them the hope of prosperity. The figure of Semar in this story has an important symbolic value, which is still adhered to by the supporting community. The other function of the story is to fulfil social and aesthetical needs.Â Keywords: Lumbung Tugu Mas story, meaning, and symbol.